Topographic Characterization of Cu–Ni NPs @ a‑C:H Films by AFM and Multifractal Analysis - Ţălu, Ştefan; Stach, Sebastian; Ghodselahi, Tayebeh; Ghaderi, Atefeh; Solaymani, Shahram; Boochani, Arash; Garczyk, Żaneta (The journal of physical chemistry. B, 2015)
In the present work three-dimensional (3-D) surface topography of Cu–Ni nanoparticles in hydrogenated amorphous carbon (Cu–Ni NPs @ a-C:H) with constant thickness of Cu and three thicknesses of Ni prepared by RF-Plasma Enhanced Chemical Vapor Deposition (RF-PECVD) system were investigated. The thin films of Cu–Ni NPs @ a-C:H with constant thickness of Cu and three thicknesses of Ni deposited by radio frequency (RF)-sputtering and RF-PECVD systems, were characterized. To determine the mass thickness and atomic structure of the films, the Rutherford backscattering spectroscopy (RBS) spectra was applied. The absorption spectra were applied to study localized surface plasmon resonance (LSPR) peaks of Cu–Ni NPs (observed around 608 nm in visible spectra), which is widened and shifted to lower wavelengths as the thickness of Ni over layer increases, and their changes are also evaluated by the 3-D surface topography. These nanostructures were investigated over square areas of 1 μm × 1 μm using atomic force microscopy (AFM) and multifractal analysis. Topographic characterization of surface samples (in amplitude, spatial distribution, and pattern of surface characteristics) highlighted 3-D surfaces with multifractal features which can be quantitatively estimated by the multifractal measures. The 3-D surface topography Cu–Ni NPs @ a-C:H with constant thickness of Cu and three thicknesses of Ni prepared by RF-PECVD system can be characterized using the multifractal geometry in correlation with the surface statistical parameters.